Semantic Field of the Word būdas in Simonas Daukantas’s Work Būdas senovės lietuvių, kalnėnų ir žemaičių and Some Stylistic Peculiarities - Dilytė, Dalia (Senoji Lietuvos literatūra, 2019)
It seems likely that Daukantas borrowed the title Būdas senovės lietuvių, kalnėnų ir žemaičių (The Character of the Lithuanians, Highlanders, and Samogitians) from Tacitus’ work De moribus Germanorum, which he cited in his work twice. The semantic field of the word mos is broad. This word encompasses numerous instances of being used to something and being skilled in something. Frequently, it has the meaning of a custom. In his Būdas…, Daukantas did not use the word paprotys ‘custom’ at all. In his text, this concept is expressed by the word įprotis ‘habit’, which is used 30 times, and the words įpratimas ‘being used to’, daba ‘nature, character, custom’, and apsiėjimai ‘ways of doing’, each of which recurs several times. In some instances, the sense of customs is conveyed by the word būdas, which is used over 50 times in the work and which corresponds to the Latin mores. In some episodes, the word būdas has the meaning of the way, rules, and means of doing something and is used instead of the adverbs šitaip or taip ‘in this way’. Elsewhere, Daukantas uses the word būdas to describe fundamental or inherent properties of a human, an animal, or a place. The meaning of natural qualities is also common to the Latin word mores. Thus, both in translating the title of Tacitus’ De moribus Germanorum as ‘Girionių būdas’ and in using the word būdas in the text of his work, Daukantas asserts he has the whole of spiritual qualities of the Lithuanian people or, in other words, national consciousness and the people’s essence in mind. He places emphasis on such aspects of the Lithuanian identity as the pursuit of freedom, courage, endurance, peacefulness, and reason. The code of spiritual requirements that dominates his Būdas… not only reveals the Lithuanians’ national consciousness but also seeks to nurture it by voicing the demand for the people of the nation to be proud of their national identity and the whole range of the qualities of the national identity, to love it, and never to renounce it. The attitude of persuasion and somewhat urgent assertion is conveyed through the form of a direct relationship with the reader, speaking in the first person that is not dry but vivid, and through the mood that is elevated, tense, excited, and based on the conviction of his own righteousness.
Keywords: Simonas Daukantas; būdas; mores